A triple-layer authentication framework with elliptic curve cryptography for securing IoT-assisted wireless sensor networks - Meshari D. Alanazi (PLoS ONE, 2025)
Wireless Sensor Networks (WSNs) are integral to the Internet of Things (IoT), yet they face significant security challenges, including vulnerabilities to various attacks like Man-in-the-Middle and insider threats. Traditional security mechanisms are often insufficient in providing the necessary level of security while accommodating the processing and energy limitations of resource-constrained devices. Hence the research proposes an innovative Elliptic Curve Cryptography and Triple-Layer Authentication Framework (ECC-TLAF) that enhances the security of WSNs while improving energy efficiency and reducing latency. The framework utilizes a lightweight authentication approach involving biometrics, smart cards, and passwords. The research results indicate that the ECC-TLAF model significantly enhances performance, achieving a 98.9% improvement in energy efficiency, a 95.6% increase in security, and a 96.7% attack detection rate. Moreover, it reduces processing time by 1.02 seconds and latency by 0.1 milliseconds compared to conventional frameworks. The ECC-TLAF framework effectively addresses the security challenges in WSNs, ensuring robust protection against cyber threats while optimizing resource utilization. This research contributes to the advancement of security protocols for IoT environments, paving the way for more secure and efficient WSN applications.